PENGARUH STRES KERJA DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN BAGIAN OPERATOR PRODUKSI PT. JAMU AIR MANCUR - Anggraeni, Della; Budiwinarto, Kim (Surakarta Management Journal, 2020)
AbstractThis study aims to determine whether there is an influence between job stress  and leadership style variables on employee performance at PT. Jamu Air Mancur ‘s production operators sector. The population of this study were employees at PT. Jamu Air Mancur’s production operators sector. And the sample are 67 employees, using census techniques. The data collection method uses a questionnaire that is measured by a Likert scale. Data tested with: (1) data quality test consists of validity test and reliability Test (2) classical assumption test consists of Normality Test, Multicollinearity Test, and Heteroscedasticity Test, (3) Hypothesis Test consists of Descriptive Statistical Analysis, Analysis Multiple Linear Regression, F-Test, t-Test, and tested of Determination Coefficient.  The results showed that job stress has a significant effect on employee performance, leadership style has a significant effect on employee performance, and job stress with leadership style simultaneously influences employee performance.